The Impact of Employee Participation in Accounting Services Outsourcing Decision: Case Study of Nigerian SMEs - Danjuma, Mohammed; Teru, Peter (European Scientific Journal, ESJ, 2017)
This paper titled the Impact of Employee Participation in Accounting Services Outsourcing (ASO) by Small and Medium Enterprises (SMEs) in Nigeria. The study seeks to identify what factors affect outsourcing decision and the relationship between employee participation and outsourcing decision by SMEs. Therefore the study is mainly guided by the theory of Transaction Cost Economics (TCE). The key arguments of this paper were developed in line with TCE Theory. Thematic analysis of 1,300 SMEs using 10 case study based on in-depth interviews with Chief Financial Officers (CFOs) representing 10 industrial sectors. The study area is North Central Geo-Political Zone of Nigeria comprising mainly profit based manufacturing SMEs excluding public not for profit and service oriented enterprises. The study found that ASO decision is affected by cost-driven, strategy-driven, environment-driven and function-driven factors which all are linked with employee attitude and behavior to work. Therefore the study concludes that employee participation has positive influence over sourcing decision by Nigeria’s SMEs. It also confirmed that communication, vendor expertise and trustworthiness are drivers of sourcing decision by these enterprises.